ANALISIS FATWA DSN-MUI NO. 25/DSN-MUI/III/2002 TENTANG RAHN TERHADAP PRAKTIK PEGADAIAN SEPEDA MOTOR - Robin, Robin; Nilhakim, Nilhakim; Miswinda, Miswinda (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2024)
This research was motivated by researchers suspecting that there was a discrepancy between the MUI DSN Fatwa Number 25 of 2002 concerning Rahn and the practice of motorbike pawning carried out by the people of Lumbang Village, Sambas District. This is because there is use of pawned goods and re-pawning to third parties which is not in accordance with Islamic law. The focus of this research problem is: first, what is the practice of motorbike pawning in Lumbang Village, Sambas District. Second, what is the analysis of DSN-MUI Fatwa No. 25/DSN-MUI/III/2002 Regarding Rahn regarding the practice of motorbike pawning in Lumbang Village, Sambas District. This research generally aims to determine the practice of motorbike pawnshops in Lumbang Village, Sambas District. and specifically to review how the analysis of DSN-MUI Fatwa No. 25/DSN-MUI/III/2002 Regarding Rahn regarding the practice of motorbike pawning in Lumbang Village, Sambas District. This type of research is qualitative-descriptive research, with a normative-empirical approach, which is used to analyze or find out to what extent regulations or laws and laws are operating effectively. The data collection techniques used were observation, interviews and documentation, based on primary data sources, namely pawnshops, recipients of pawned goods and holders of pawned goods who practice motorbike pawning in Lumbang Village, Sambas District and the secondary data source in this research is the DSN-MUI Fatwa No. 25/DSN-MUI/III/2002 Regarding Rahn. Based on the research results, it can be concluded that the practice of motorbike pawning in Lumbang Village, Sambas District does not comply with the provisions in DSN-MUI Fatwa No. 25/DSN-MUI/III/2002 Regarding Rahn. This is due to additional costs, there are two types of additional costs charged to Rahin. First, Rahin must pay interest of 5% / 6 months on the pawn debt if Rahin is late in paying the pawn debt. Second, Rahin was charged interest of Rp. 200,000/month until he is able to pay off his debt. Based on this, the practice of motorbike pawning carried out by the community in Lumbang Village contains elements of usury. As is known, in Islam debts cannot increase or have interest, because if the debt is an interest-bearing debt then the agreement is already an agreement containing elements of usury, whereas this act of usury is prohibited in Islam.